Predictors of Retinopathy of Prematurity Reactivation in Pakistani Preterm Neonates After Anti-VEGF Therapy: Retinopathy of Prematurity Reactivation: Anti-VEGF Therapy - Jatoi, Asadullah; Memon, Mariya Nazish; Mahesar, Mona Liza; Gilal, Imtiaz; Memon, Shazia; Narsani, Ashok Kumar; Maisam, Muhammad (Pakistan Journal of Health Sciences, 2025)
Retinopathy of prematurity (ROP) is a significant cause of preventable childhood blindness, particularly in low- and middle-income countries like Pakistan, where preterm survival rates are increasing. However, the risk of disease reactivation after initial regression remains a concern, particularly in settings with limited follow-up infrastructure. Objectives: To determine the incidence and identify clinical predictors of ROP reactivation among Pakistani preterm neonates treated with intravitreal anti-VEGF therapy. Methods: This observational study was conducted at the Neonatal Nursery of the Pediatric Ward, Liaquat University of Medical and Health Sciences, Jamshoro. A total of 47 preterm neonates (≤34 weeks’ gestational age and/or ≤2000 grams’ birth weight) who received anti-VEGF injections for treatment-requiring ROP were consecutively enrolled. Data on ROP zone, stage, gestational age, birth weight, and anti-VEGF agent were collected. Follow-up was performed to assess reactivation, defined as recurrence of plus disease or disease progression necessitating retreatment. Statistical analysis was performed using SPSS 25.0. Results: The mean gestational age and birth weight were 29.5 ± 1.5 weeks and 1250 ± 200 grams, respectively. ROP reactivation occurred in 8 of 47 neonates (17.0%). Zone I disease was significantly associated with higher reactivation risk (p=0.029). No significant associations were found with ROP stage, anti-VEGF type, or gestational age. Conclusions: ROP reactivation following anti-VEGF treatment occurred in 17% of cases. Zone I involvement was the only significant predictor, highlighting the need for vigilant long-term follow-up in these patients.